Dodeca-Helix: Pentingnya Mengintegrasikan 12 Dimensi Pemangku Kepentingan untuk Menumbuhkan Ekosistem Inovasi di Kota Baubau - Saksono, Herie (Balitbangda Kota Baubau, 2024)
The evolution of innovation models in regional development has progressed from Triple-Helix to more complex models, yet gaps remain in accommodating the roles of various stakeholders in regional innovation ecosystems. This research examines how the Dodeca-Helix model can integrate 12 stakeholder dimensions to foster innovation ecosystem in Baubau City. Through a qualitative approach with descriptive analysis method, the research was conducted in four stages: literature study, stakeholder mapping, conceptual framework development, and empirical validation. Data collection was carried out through document analysis and regulations related to regional innovation. The results show that the implementation of the Dodeca-Helix model contributed to the improvement of Baubau City's status from